Peningkatan Pemahaman Kepribadian Diri Mahasiswa Bimbingan dan Konseling dengan Penugasan Essai Refleksi - Bella Fazny (Kuras Institute, 2022)
The learning strategy of giving evaluation quizzes is considered less appropriate in increasing students' understanding of personality psychology course material. Based on the results of the evaluation quiz scores for the post-presentational group presentation, it is known that an average of 85 students scored below 70. This condition confirms the failure to achieve the learning objectives of the personality psychology course, namely providing insight into understanding as well as providing the counselor with basic skills of self-reflection to be able to empathize with various types. own personality. Classroom action research (CAR) successfully conducted a SWOT analysis of the implementation of the development of self-reflection essay assignments on 85 students of Islamic guidance and counseling. Self-reflection essays are recommended in personality psychology classes. Students are given many challenges to see their strengths and weaknesses. Self-reflection essays can also be an opportunity for prospective counselors to identify and recognize issues of self-unfinished business in order to avoid negative transference countertransference personal issues. Suggestions for further PTK researchers include being able to try out the method of assigning self-reflection essays to other subjects that are still of the same scientific background, such as the introduction of the basic competencies of a guidance and counseling counselor and the counselor's code of ethics.